The Influence of Health Education on The Knowledge of Grade IX Female Adolescents about Sexual Violence at SMP X Bekasi - Rahel Agustin Fajar; Indah Yuliani (Universitas Malahayati, 2026)
ABSTRACT Sexual violence against adolescent girls remains a critical public health issue with severe physical, mental, and social consequences. Indonesian Health Survey (2023) data reveals concerning prevalence rates among girls aged 14-17: 15% experienced verbal sexual harassment, 8.5% physical harassment, and 3.2% severe sexual violence. Bekasi City witnessed increased cases from 65 (2021) to 87 (2022). Previous research indicated 68.3% of female adolescents in Bekasi had inadequate knowledge about sexual violence, with 85.7% never receiving specific school-based health education on this topic. To analyze the effectiveness of health education intervention on ninth-grade female adolescents' knowledge regarding sexual violence at SMP X Bekasi. Methods: A quasi-experimental pre-post test design was employed with ninth-grade female students selected through purposive sampling. Knowledge levels were assessed using a validated questionnaire administered before and after health education intervention. Statistical analysis determined pre-post intervention knowledge differences. Normality testing revealed non-parametric distribution of pre-test and post-test data (p0.05), requiring non-parametric statistical analysis. Significant improvement in adolescent girls' knowledge about sexual violence was observed post-intervention, demonstrating enhanced understanding of definitions, forms, risk factors, and prevention strategies. Health education intervention effectively enhanced adolescent girls' knowledge about sexual violence. Implementation of comprehensive school-based health education programs is crucial for primary prevention of sexual violence against adolescent girls. Keywords: Health Education, Knowledge, Sexual Violence, Adolescent Girls, Prevention.